Investigating the role of the SNARE-associated protein Snapin in human THP-1 macrophage immune response during M. tuberculosis infection - Brown, Nicole Karen (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.